Rising cost of living in Nigeria: implications on the welfare of aged women (2023)
This paper delves into the impact of rising living costs on older women, using empirical evidence and theoretical frameworks to elucidate the complex ramifications of financial strain. Aged women are chosen for examination due to their vulnerability to economic hardships, stemming from fixed incomes and increased healthcare needs. The study aims to illuminate the specific challenges faced by elderly women amidst economic turbulence, emphasizing the importance of safeguarding their welfare for societal stability. It highlights the significance of addressing the welfare concerns of elderly women within the context of escalating living expenses, emphasizing tailored interventions to protect their well-being. The rising cost of living is characterized by a persistent increase in the prices of essential goods and services, dri ven by factors such as inflation and currency devaluation. This phenomenon affects elderly women in various ways, including financial distress and limited access to healthcare. Direct consequences include heightened economic adversity and decreased purchasing power, while indirect effects extend to the broader population through disrupted family dynamics and strained support systems. Recommendations for mitigating these impacts include targeted social welfare initiatives and enhanced healthcare access, with anticipated benefits including improved financial stability and social integration for elderly women, ultimately contributing to a more equitable and resilient society.